The content marketing handbook : how to double the results of your marketing campaigns - Bly, Robert W. (Entrepreneur Media, Inc., 2020)
"Content can be an effective and economical tool to add to your marketing strategy. But content marketing is most effective when integrated into a multi-channel campaign that not only educates consumers but offers that content with various direct response methods, online and offline, to generate leads, prospects, and direct sales. Having written more than 90 books during his forty-year career in content and direct marketing Robert W. Bly has more than a few strategies to help readers get the highest ROI on their content"--